The Influence of Ramadan Fasting on Some Hematological and Biochemical Parameters in Healthy Adult Males - mohammed, Zahid (Iraqi National Journal of Nursing Specialties, 2011)
Objective(s): Ramadan is the Holy month of the Muslims, where they are required to abstain from food and drinksfrom dawn till the beginning of night. This study was conducted in Ramadan to investigate the effect of fasting onhematological incidences, lipid profile, renal and liver function tests among healthy adult males.Methodology: The present study was carried out in Ramadan – 1431 of Higira (August-September 2010). The studysample was 56 healthy adult males. Five samples of blood were taken at five intervals (Before, at day 1, 15, 28 andafter Ramadan). Estimation was done for hematological markers, (hemoglobin, white blood cells count, plateletcount); renal function tests (blood urea, serum uric acid, serum albumin, total serum protein); biochemicalparameters, (blood glucose, total serum cholesterol, serum triacylglyceride, high and low density lipoproteins) andliver function tests (AST, ALT, Alkaline phosphatase, total serum bilirubin).Results: The mean age of the subjects was 48.4 years (SD 7.15) and mean weight was 79.92 kg (SD 7.94). Nosignificant changes were observed in weight, hemoglobin, white blood cell count and platelets count, blood urea andserum albumin values. Whereas, serum uric acid and total serum protein levels were statistically lower during andaŌer Ramadan (P< 0.05, 0.01).Blood levels of glucose showed no significant decrease and serum cholesterol and serum triacylglyceride results werenon-significant at first 2 weeks of Ramadan.The same significant changes (p< 0.05, 0.01) were observed in the lipoprotein at day 15 and 28 of Ramadan. Findingsof liver functions levels showed significant changes. While, total serum bilirubin still with no significant changes duringRamadan.Recommendations: The present study recommends performing more studies with both larger groups and in variouscategories of healthy and unhealthy subjects.